Comparison of drift eliminators characteristics in evaporative condenser and spray-filled tower - Mohiuddin, A. K. M.; Saidur, R.; Sattar, M.A.; Rahman, Mohammed Ataur (REGIONAL ENERGY RESOURCES INFORMATION CENTER (RERIC), Asian Institute of Technology (AIT), 2007)
This paper investigates the results of experimental studies conducted in an evaporative condenser with induced draft and in a spray filled forced draft cooling tower. The pressure drop and drift loss characteristics of cement-asbestos drift eliminators, concrete drift eliminators, wooden drift eliminators and cellular type drift eliminators were experimentally investigated. The experiments were conducted with one, two, and three stages of cellular type drift eliminators but for cement-asbestos, concrete and wooden drift eliminators only two and three stages were used with various orientation angles (θ) of the eliminator plates. The results showed that the drift loss for CTDE decreases with the increase of the number of stages and with decrease of flow rate whereas drift loss for CADE and CDE also decreases with decrease of orientation angle, θ .The pressure drop for CTDE is smaller than that for CADE and CDE in the practical range of θ. In this study, the superiority of the cellular type drift eliminators over the others has been divulged.